Experimental research into the mutagenic mechanism of Thiobacillus Ferrooxidans - Liu, Yu-de (2013)
The thiobacillus ferrooxidans(T.f) 's growth characteristics and mutagenic mechanism under the action of the ultraviolet radiation was studied.T.f was irradiated for 300 s by ultraviolet lamp with 20 W.The redox potential and pH in etching liquid were measured every 15 s.The pH history and redox history were given,respectively.The optimal values of the redox potential and pH were 303 mV and 1.98 respectively when T.f was irradiated for 240 s.The mutagenized and strengthened T.f possesses of the better etching ability.It also has higher bacterial concentration and stronger oxidation active.The minigear structure is more distinct by using mutagenized T.f etching.